PARADOXICAL ASSESSMENTS AND INTERPRETATIONS OF M. HOHOL’S CHRISTIAN ANTHROPOLOGY - Mozgova, Natalia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. Mykola Hohol is one of the most controversial figures in the native culture of the XIX century because of endless discussions like: Did Hohol gravitate more towards Westerners or Slavophiles according to his preferences? Did he or did he not experience the spiritual drama that led to a revolution in his worldview, which, in turn, found its expression in his radical departure from fiction and complete immersion in the search for religious truth? Perhaps this search for religious truth was characteristic of Hohol since his childhood, and only in the course of time did he finally free himself from the captivity of the writer’s artistic talent and develop in the field of religious preaching. The aim of the study is to theoretically reconstruct the speculative searches for the foundations of M. Hohol’s Christian anthropology. This goal is realized in the following tasks: to analyze the texts of those works of the writer, which show the formation of the writer’s religious identity; to identify the socio-historical conditions in which the foundations of M. Hohol’s ideological and religious views were formed; to show the paradoxical and contradictory interpretation of M. Hohol’s Christian anthropology by contemporaries and descendants; to compare the latter with those theoretical provisions of the present that remain relevant nowadays. In the process of this research, the following methods were used: hermeneutical method – to interpret and explain the authentic methods of historiographical analysis, to systematize primary sources and scientific literature devoted to studying the creative heritage of M. Hohol; comparative-historical method – to identify socio-historical conditions under which the writer’s religious world-view was formed; comparative analysis – to compare the ideological, philosophical and religious preferences of M. Hohol with his contemporaries; a method of textual analysis – in order to take into account the context in studying the creative heritage of the XIX century. Along with this, such general scientific methods as comparison, analysis, and synthesis, induction and deduction, abstraction and concretization, etc. played an important role. Conclusions. It should be emphasized that only at the turn of the XIX and XX centuries did a radically new vision of Hohol’s creativity appear and establish itself in the works of M. Berdyaev, V. Zavitnevych, V. Zenkovskyi, H. Florovskyi, S. Frank and others. But this vision was most clearly expressed by V. Rozanov saying that M. Hohol seemed to be struggling with a sad reality; half of his activities have remained incomprehensible within him with such a view; he remains incomprehensible entirely as a person, with his painful wanderings from country to country, with the thirst to escape from his native land, with prayers, asceticism, the journey to Jerusalem, the burning of the volume of "Dead souls". What do we care about him (italics by V. Rozanov – N. M.); after all, he became an assistant to us. But a great man is worth considering him/her within him-/herself. In the history of his soul, at least a single one, he can be more significant than the whole society as a whole with the history of their small worries, excitations, hopes, anger" (Rozanov 1990, 192).